Influence of activated carbon as filler on the mechanical properties of wood composites by using solidworks simulation and experimental methods - Nor Atikah, Abd Aziz (2015)
This study is conducted to investigate the influence of activated carbon as filler on the mechanical properties of wood composite. It mainly focused on the strength, stress, and displacement of the wood composites. A composite material is defined as a combination of two or more materials that results in better properties than the individual components are used alone. The wood composite have certain advantages over wood, as they are affordable and have the potential for versatile designs. The materials possess good mechanical properties and have a long service life. Due to the excellent of mechanical properties, wood composite materials have been widely used throughout the last four decades. Structural and non-structural engineered wood composites based on plywood, medium density fibreboard (MDF), laminated veneer lumber (LVL), thermoplastic or wood fiber blends, and are now used in both interior and exterior applications. The advances existing technology, especially in engineering field in which the use of computer software such as solid work simulation is used to test model digitally for valuable technical insight early in the design process. This type of software reduces weight and materials cost, improve durability and manufacture ability of the product. Simulation also enables representation of the modelled real system and its behaviour in real time by means of computer. Both simulation and experimental method used in this study, MDF composite samples show higher strength value than plywood composite samples due to the increasing of thickness of the activated carbon filler. Overall, the percentage differences between simulation and experimental method is lower than 10% which indicate that simulation is suitable tool use to predict the strength of wood composites.